Safety & Efficacy of Propranolol and Amitriptyline Combination Therapy in Migraine Prophylaxis: A Randomized Control Trial (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Combination of propranolol and amitriptyline drugs an be effective for migraine prophylaxis.Objective: The purpose of the present study was to see the safety and efficacy of propranolol and amitriptyline combination therapy in migraine prophylaxis.Methodology: This study randomized control trial was conducted in headache clinic at Banghabandhu Sheikh Medical University (BSMMU), Dhaka, Bangladesh from July 2012 to June 2014 for a period of two (02) years. Migraine patients with or without aura of 16 to 50 years of age, patients not on any prophylactic medication and patients willing to take part in the study were included for this study. Patients meeting all the criteria was randomized for two (02) treatment groups designated as the group A who were treated with Amitriptyline and the group B who were treated with the combination of amitriptyline and propranolol. Patients was followed for a three months period during which they were instructed to maintain a headache diary. The primary outcome evaluated was the proportion of patients in each group that achieved a 50% reduction in the number of days with headache. Secondary outcomes was reduction of visual analogue pain scale score, the number of days with headache per month, frequency of side effects and the proportion of patients abandoning the study before the end of medication. The causes of noncompliance and side effects was individually registered.Result: A total number of 8 0patietns were recruited for this study. During 1st visit among the patients in group A, duration of pain 1-4 hours 1 (2.5.0%), 5-8 hours 16(13.3%) and 9-12 hours 14(35.0%). In group B, duration of pain 1-4 hours 0(0.0%), 5-8 hours 18(15.0%) 9-12 were 21(52.5%), above 13 hours pain duration were 1(2.5%) (p>0.05). Duration of pain was recorded in final follow up among the patients. In group A, duration of pain 1-4 hours 24(60.0%), 5-8 hours 14(35.0%), 9-12 hours 2(5.0%). In group B, duration of pain 1-4 hours 28(70.0%), 5-8 hours 12(30.0%), 9-12 hours were not found (p>0.05). In group A, no adverse effect was found 26(65.0%), drowsiness 6(15.0%), dryness of mouth 6(15.0%), constipation 2(5.0%), fatigue and bradycardia were not found. In group B, no adverse effect was found 29(72.5%), drowsiness, dryness of mouth and constipation were not found, fatigue and bradycardia were 7(17.5%) and 4(10.0%). Number of attack and headache before treatment and subsequent follow up with medication it was found that number of attach and headache gradually decrease (p